DAMPAK PENCEMARAN SUNGAI TERHADAP EKOSISTEM DAN KEHIDUPAN WARGA: PENDEKATAN MIXED METHOD - Fitra Dika Pakpahan; Hendra Taufik (MARSEGU : Jurnal Sains dan Teknologi, 2026)
River pollution is a critical environmental issue that significantly affects aquatic ecosystems and the socio-economic conditions of communities. This study aims to analyze the impacts of river pollution on ecosystems and community livelihoods using a mixed methods approach with a sequential explanatory design. The study was conducted from August 2025 to January 2026, aligned with the dry season to minimize rainfall variability affecting water quality parameters. Laboratory analysis was carried out at the Laboratory of Universitas Riau, examining seven water quality parameters across five sampling points along the river, including BOD, COD, DO, pH, total coliform, lead, and cadmium. Structured questionnaires were distributed to 80 riparian residents, while in-depth interviews were conducted with 15 purposively selected informants. The results indicate that water quality in the middle to downstream zones has exceeded the permissible limits set by Government Regulation No. 22 of 2021, with a Water Quality Index (WQI) score of 28.4 in the downstream zone, categorized as very poor. The Shannon-Wiener biodiversity index declined sharply from 2.87 in the upstream area to 0.72 downstream, indicating the collapse of the aquatic ecosystem due to hypoxia and heavy metal accumulation. A total of 76.3% of respondents reported difficulties in accessing clean water, and 47.5% experienced a decline in income exceeding 50%. Thematic analysis identified four main themes: ecological awareness, economic burden, structural powerlessness, and adaptive strategies. This study concludes that river pollution has caused severe ecological degradation and socio-economic hardship that reinforce each other, highlighting the need for integrated, evidence-based, and participatory policy interventions.